Tawẓīf ṭarīqah al-ta'allum al-qā'im ʿalā al-mashrū' fī tadrīs 'ilmi albayān bi wāsiṭah al-yūtiub توظيف طريقة التعلم القائم على المشروع في تدريس علم البيان بواسطة اليوتيوب - Azman, Yusra; Chik, Abdul Rahman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The level of students’ proficiency in rhetoric remains low from one of the questionnaires. The rhetoric material that the students learned was unclear, ineffective, frustrating, and boring. This is due to the difficulties of learning rhetoric, and the inappropriate method and tool for teaching students. As a result, the significance of this research stems from determining the efficacy of the YouTube method and the project-based learning method in terms of attracting students' attention and motivating them to participate in the teaching and learning process. This sample consists of six registered female students in Methods of Teaching Arabic as a Second Language subject. The study followed the inductive and applied descriptive approach, describing the concept of rhetoric, YouTube, and the project-based learning method scientifically in light of this phenomenon, and then applying this theory by conducting micro-teaching by employing YouTube in teaching rhetoric through the project-based learning method. The study concluded that the project-based learning method and the YouTube method are appropriate for teaching rhetoric because they draw students' attention to the lesson and stimulate their motivation to actively participate in the educational and learning process. The researcher noticed that the students interact well and participate in microteaching with positive and active participation, as they can understand more of the directions and lessons.